The Effects of Company CSR on Generation Z – Example of an Insurance Company - Nevenka POPOVIĆ ŠEVIĆ; Milica SLIJEPČEVIĆ; Milena ILIĆ (Communications of International Proceedings, 2020)
The purpose and the objective of this paper are to examine the essence of the social responsibility concept by way of an example of a respected Serbian company doing business in the insurance industry, with a special focus on the opinions and attitudes of Generation Z. The objective of this paper is to examine the availability of information concerning CSR activities in the local community, as well as the broader one, with a special emphasis on its development, as well as aid in the spheres of culture, science, and education, sports and assistance for the socially disadvantaged. This objective is to be achieved using quantitative research and individual interviews. The road to a proper strategic direction is paved by linking company work with responsible business and adequately communicating with target audiences. This paper underlines the significance of informing the target population factually and in a timely manner, resulting in comprehensive and transparent information about the CSR activities undertaken in the insurance industry.
Keywords: Socially Responsible Business; Organisational Support; Business Competitiveness; Generation Z; Insurance Industry